BCS partner: from Cats Protection to data protection. (11th January 2022) - Adams, Kevin
Abstract: Kevin Adams and his team at Cats Protection rose to the challenges that COVID-19 brought to the charity's rehoming processes… and discovered a nice shade of green along the way.